Diagnostic errors in Dentistry, opinions of egyptian dental teaching staff, a cross-sectional study - Naglaa El-Wakeel; Naglaa Ezzeldin (BMC, 2022)
Abstract Background Diagnostic errors is a known problem in healthcare practice. Data on diagnostic errors in the dental field are extremely lacking. The objective of the study is to explore the perception of dental teaching staff about the prevalence of dental diagnostic errors in Egypt, identify the most commonly misdiagnosed dental conditions and point out the contributing factors and levels of patient harm. Methods A cross-sectional questionnaire-based study was conducted on 151 dental teaching staff of Egyptian governmental and private universities. The questionnaire was distributed electronically via social media and messaging apps to dental staff members with at least five years of clinical experience to assess their opinion regarding the study objectives. Results were collected and statistically analyzed. Results 94.7% of participants believed that diagnostic errors represent an urgent problem, lecturers believed by 2.703 folds more than professors that diagnostic errors are an urgent problem The percentage of diagnostic errors was estimated to be < 20% and 20-40% by more than 90% of participants. The most commonly misdiagnosed conditions were oral mucosal lesions (83.4%), followed by temporomandibular joint and periodontal conditions (58.9%) for each. More than half of the participants (60.9%) believe that medical education methodology is one of the factors that lead to dental diagnosis errors. For the impact of errors on patients, 53% of participants reported moderate impacts followed by minor impact (37.7%) while 4.6% reported no impact and the same percentage reported major impact. Conclusion This study with statistically significant results reported that dental diagnostic errors are frequent and need to be approached. Oral mucosal lesions, periodontal and temporomandibular joint diseases represent areas that include the most commonly seen errors. Further, besides the lack of resources, the dental education system and lack of proper training are the main causes of this problem.